Quantitative Assessment of Prewriting Skills in Children: The Development and Validation of a Tablet Assessment Tool. Issue 3 (June 2022) - Chu, Virginia; Krishnan, Kavitha
Our purpose in this study was to determine the feasibility of assessing children's prewriting with a new tablet tool, the Quantitative Assessment of Prewriting Skills (QAPS), while determining the validity of the QAPS for identifying visual motor skill differences. We recruited 10 children who were receiving occupational therapy (OT) services for visual motor deficits from a local OT clinic and 10 age-matched typically developing (TD) children from the local community. The QAPS assesses the accuracy of copying patterns on a tablet that records the child's finger position on the tablet, and the data are then analyzed for different dimensions of pattern copying. We found a large effect size difference in the QAPS total score between our two participant groups, with the OT group showing poorer performance than TD children; and, among nine assessment dimensions, roundness of a drawn circle showed the largest effect size difference between groups. The QAPS appears to be a promising tool for assessing visual motor skills, and it warrants additional testing in larger participant samples.